Let's simplify step-by-step.
w−(y−x)−1
=w+−y+x+−1
=w+x−y−1
Description:
Since this is a small equation the first step is to simplify the equation at the end your answer will end up as w+x−y−1.
The first step is to simplify the equation step by step and to simplify an equation you can first multiplying the factors and use the exponent rules to remove the parentheses. After that your answer will come as =w+x−y−1. Since this is a small equation you don't need to combine like terms. So
w-(y-x)-1 = w+x−y−1.
Answer: =w+x−y−1
Hope this helps.